Pemberdayaan kader posyandu melalui penerapan metode konseling gizi dan komunikasi efektif - T Khairul Fadjri; Teuku Jamni (Politeknik Kesehatan Kemenkes Aceh, 2020)
Background: The relatively low level of education as well as public knowledge and awareness in the health sector is the main cause of nutritional problems in children under five. One of the steps that can be taken to help this problem is to increase the resources of Posyandu cadres as the frontline in handling nutritional problems at the rural level through nutritional counseling activities and effective communication.Purpose: This research aims to increase the nutrition knowledge of Posyandu cadres about nutritional counseling and effective communication in an effort to improve Posyandu services.Methods: This community service is carried out through training on nutritional counseling and effective communication for Posyandu cadres with counseling and training methods, question and answer and role play.Results: Posyandu cadre knowledge shows perfect improvement after training, cadres' knowledge of material understanding is generally good, most (80.0%) Posyandu cadres already have good effective counseling and communication skills.Conclusion: Posyandu cadres are able to understand and apply the concept of nutritional counseling and the concept of effective communication as well as changes in attitudes and behavior of Posyandu cadres regarding the nutritional problems of toddlers